If x + y + x + y = 4 2 and x − y + x − y = 2 0 , then find the sum of all possible values of x y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Correct. A common error is to accidentally include one or more of the extraneous solutions. After all, they do seem to fit in to the quadratic equation... However, a quick glance back at our original equation and we see that it is not possible.
I think there is a typo;
"The solutions for this are
b
=
1
6
,
2
5
..... "
You fixed it in the next line, but it was confusing for a second.
Either way, this is a really nice solution.
Log in to reply
Yes, you are correct.
By the way, we can substitute u = x + y , which will a little bit faster, since we can quickly determine the value of x + y . The same thing goes for x − y . This is how I do it.
Let u = x + y and v = x − y . We then have,
u 2 + u = 4 2
⟹ u = 6 , − 7
after some easy factorization. Similarly, by using the style above, we will have
v 2 + v = 2 0
⟹ v = 4 , − 5
But since negative numbers are not possible for the square roots, so u 2 = x + y = 3 6 and v 2 = x − y = 1 6 . Solving the simultaneous equation, we arrive x = 2 6 and y = 1 0 , implying to our desired answer which is x y = 2 6 0 .
Because I see a substitution in the first equation, let a = x + y . The equation then becomes a + a = 4 2 ⇒ a = 4 2 − a ⇒ a = a 2 − 8 4 a + 1 7 6 4 ⇒ a 2 − 8 5 a + 1 7 6 4 = 0 ⇒ ( a − 3 6 ) ( a − 4 9 ) = 0 ⇒ a = 3 6 , 4 9 . Since square roots were involved, we must check the solution.
If a = 3 6 , then 3 6 + 3 6 = 4 2 , which is creary true. If a = 4 9 , then 4 9 + 4 9 = 4 2 , which is creary not true.
Therefore, we have x + y = 3 6 .
Approaching the second equation the same way, let b = x − y . Then, b + b = 2 0 ⇒ b = 2 0 − b ⇒ b 2 − 4 1 b + 4 0 0 = 0 ⇒ ( b − 1 6 ) ( b − 2 5 ) = 0 . Checking, we see that 25 is an extraneous root, and 16 is our only root.
Therefore, x + y = 3 6 and x − y = 1 6 . Adding these equations, we have 2 x = 5 2 ⇒ x = 2 6 ⇒ y = 1 0 .
Now we must multiply 26 and 10. This is quite hard, but with a calculator, we get 2 6 ⋅ 1 0 = 2 6 0
what if 49^0.5 is taken as -7 ?
Log in to reply
That's not possible because you cannot take the square root of a negative number.
Minimario, you never fail to amuse me :)
You didn't have to expand a+a^0.5 =42 , you could've simply taken a^0.5= p then solved p^2 + p = 42 The same for the 2nd equation
Lets say x + y = a and x − y = b . Then the equations turns to:
A ) a + a − 4 2 = 0 → a = 4 9 or a = 3 6 .
B ) Similarly, b + b − 2 0 = 0 → b = 2 5 or b = 1 6 .
We equal:
x + y = 4 9 or x + y = 3 6
x − y = 2 5 or x − y = 1 6
We have 4 possible system of equations. Solving them, we get the folllwing possible values for x and y :
( 2 6 5 , 2 3 3 ) , ( 3 7 , 1 2 ) , ( 2 6 , 1 0 ) and ( 2 6 1 , 2 1 1 ) . Substituting them on the original equations, the only one that satisfies the system with the principal square roots is ( 2 6 , 1 0 ) . Finally, x y = 2 6 ∗ 1 0 = 2 6 0 .
(x+y)^{1/2}=a -> a^{2}+a=42 -> a=-7 or a=6... (x+y)^{1/2}=6 and not -7... -> x+y=36
(x-y)^{1/2}=b -> b^{2}+b=20 -> b=-5 or b=4... (x-y)^{1/2}=4 and not -5... -> x-y=16
x+y=36
x-y=16
so x=26 & y=10 -> xy=260
m+\sqrt(m)=42 n+\sqrt(n)=20 EXPANDING WE GET m^2+m-1764=0 solving we get the answer
Problem Loading...
Note Loading...
Set Loading...
Let x + y = a . From the first equation, a + a = 4 2 The solutions for this are a = 3 6 , 4 9 , but 49 is extraneous due to the square root, so x + y = 3 6 .
Let x − y = b . From the second equation, b + b = 2 0 The solutions for this are b = 1 6 , 2 5 , but 25 is extraneous due to the square root, so x − y = 1 6 .
Thus, x = 2 6 and y = 1 0 , so the answer is 2 6 ⋅ 1 0 = 2 6 0 .